2006
DOI: 10.1111/j.1365-2621.2005.tb07187.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality and Functional Characteristics of Chungkukjang Prepared with Various Bacillus sp. Isolated from Traditional Chungkukjang

Abstract: ABSTRA ABSTRA ABSTRA ABSTRA ABSTRACT CT CT CT CT: : : : : B B B B Bacillus cir acillus cir acillus cir acillus cir acillus circulans culans culans culans culans, , , , , B B B B Br r r r revibacillus br evibacillus br evibacillus br evibacillus br evibacillus brevis evis evis evis evis, , , , , B. . ster ster ster ster sterothermophillus othermophillus othermophillus othermophillus othermophillus were isolated and identified from chungkukjangs (Korean traditional soybean paste fermented for a few day).were iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 12 publications
3
29
0
Order By: Relevance
“…Glutamic acid, arginine and lysine accounted for 40% to 50% of the total 7S hydrolysates and 35% to 42% of the 11S hydrolysates in this study. Increases in glutamic acid, aspartic acid, arginine, and glycine in chungkukjang can improve sweet and savory taste characteristics (Lee et al, 2005). Aspartic acid and glutamic acid belong to the acidic amino acid group, accounting for more than 44% of both 7S and 11S globulins.…”
Section: Discussionmentioning
confidence: 99%
“…Glutamic acid, arginine and lysine accounted for 40% to 50% of the total 7S hydrolysates and 35% to 42% of the 11S hydrolysates in this study. Increases in glutamic acid, aspartic acid, arginine, and glycine in chungkukjang can improve sweet and savory taste characteristics (Lee et al, 2005). Aspartic acid and glutamic acid belong to the acidic amino acid group, accounting for more than 44% of both 7S and 11S globulins.…”
Section: Discussionmentioning
confidence: 99%
“…The peptides from soybean, rice bran, oil seeds, seafood, milk and other dairy products have been extensively studied as the promising precursors of the bioactive peptides (Wenyi & Elvira, 2005;Gibbs et al, 2004;Yoshikawa et al, 2003;Floris et al, 2003). Also, several reports have indicated that fermented chungkukjang showed stronger antimutagenic effects than nonfermented cooked soybeans (Lee et al, 2005;Chung et al, 1997;Ko et al, 1996;Kwon et al, 2002;Park et al, 2001). However, little research has been done on the antioxidant properties of chungkukjang derived peptides.…”
Section: Soybean (Glycine Max L) Contains Approximately 40mentioning
confidence: 99%
“…Chungkukjang is produced by fermentation with a cooked soybean, but their quality are varies considerably with soybean varieties, fermenting bacterial strains, fermentation time, sub-ingredients, and so on (Lee et al, 2005).…”
Section: Soybean (Glycine Max L) Contains Approximately 40mentioning
confidence: 99%
“…Bacillus species have been predominantly isolated from the fermented soybeans (SARKAR & TAMANG, 1995;LEE et al, 2005;LI et al, 2007). The high numbers of Gram-positive, endospore-forming bacilli were also detected in Thua Nao from the beginning throughout the fermentation period (CHANTAWANNAKUL et al, 2002;CHUKEATIROTE et al, 2006).…”
Section: Proteolytic Activity Production Of Bacillus Strainsmentioning
confidence: 99%
“…Many Bacillus species have been isolated during the production process as well as from the fi nal products, suggesting their abundance. Bacillus subtilis in particular has been identifi ed in Chungkukjang (LEE et al, 2005), Douchi (LI et al, 2007), Kinema (SARKAR & TAMANG, 1995), Natto (KIUCHI & WATANABE, 2004), and Thua Nao (CHANTAWANNAKUL et al, 2002). Due to a protein-rich nature of soybean, proteolysis is defi nitely a key mechanism of the fermentation.…”
mentioning
confidence: 99%